The Body Electric : How Strange Machines Built the Modern American. - De la Pena, Carolyn Thomas (American history and culture., 2003)
Between the years 1850 and 1950, Americans became the leading energy consumers on the planet, expending tremendous physical resources on energy exploration, mental resources on energy exploitation, and monetary resources on energy acquisition. A unique combination of pseudoscientific theories of health and the public's rudimentary understanding of energy created an age in which sources of industrial power seemed capable of curing the physical limitations and ill health that plagued Victorian bodies. Licensed and "quack" physicians alike promoted machines, electricity, and radium as invigoratin.